Violence against women : epidemiology and pathology of femicides and suspected sexual homicides in Cape Town : a 10-year follow-up study - Molefe, Itumeleng (Division of Forensic Medicine and Toxicology, 2016)
Background: Violence against women (VAW) is the most pervasive human rights abuse and a global health threat. The most extreme forms of physical and sexual violence are the intentional killing of a woman (femicide) and rape, or the combination of both in the form of r ape homicide, preferably termed 'sexual homicide' in this study. Motivation: Martin's research in 1999 reported a rape homicide incidence rate of 12.3/1000 female rapes reported to the police in Cape Town while the National study performed by Abrahams et al in 1999 reported an incidence rate of 10.9/1000 female rapes reported to the police in South Africa (SA). These high incidence rates, definitional problems, methodological limitations, changes in the law, and inconsistent management of suspected sexual homicides motivated the author to undertake this follow - up study. Objectives: To describe the epidemiology and pathology of femicides in Cape Town and thereby identify risk factors, magnitude and criteria for suspected sexual homicides. Design and Methodology : This is a retrospective descriptive study. Data was collected from autopsy reports of female bodies admitted at Salt River Forensic Pathology Laboratory in Cape Town from the years 2000 to 2009. A 10 - year period improves the sample size and the validity of the results. Limitations : Time constraints led to inadequate information on perpetrators of femicides and therefore a report on intimate femicide is limited in this study. Main findings and Discussion: Results showed an average femicide incidence rate of 12.4/100,000 female population in Cape Town Western Metropole which is half the South African national incidence for 1999, equates to the 2009 national rate and is almost five times the global average. Sexual homicide was suspected in 19.9% of all femicides, slightly higher than the 16.3% previously reported by Martin for Cape Town. The median age of victims was 32 years. Most femicide victims died from gunshot injuries (35.2%) followed by those who were stabbed (29.6%), while the majority (35.7 %) of victims of suspected sexual homicide died from asphyxial deaths, including strangulation. Taking specimens for the Sexual Assault Evidence Collection Kit correlated significantly with genital (77.7%) and anal injuries (64.5%), and 41% of femicide victims had alcohol levels above 0.05g%. Conclusion: The incidence of femicide and sexual homicide in Cape Town is higher than previously reported. Gun violence and alcohol abuse are persistent problems. Recommendations : Findings should be used to motivate for intersectoral collaboration in the form of female homicidal death review (FHDR) teams. These teams should aim to develop standardised guidelines for the forensic management, prosecution, prevention and monitoring strategies for femicides and sexual homicides in South Africa.